FORMATION OF THE STRATEGY OF BANKING RESTRUCTURING IN UKRAINE - Мамедов, Сергій (Socio-economic relations in the digital society, 2019)
Strengthening the processes of globalization and fi nancial integration in the modern world potentially increases the likelihood of the emergence and spread of crisis phenomena, triggering new challenge sand threats both at the level of national economies and incertain spheres. In these circumstances, the task of developing effective managerial decisions and the formation of a system of measures for the restructuring of domestic banks that perform the function of preserving public capital is updated, therefore, their fi nancial stability and reliability are subject to particularly high requirements. Th e necessity of forming a strategy of restructuring banks in Ukraine due to the imperfection of existing legal documents, the prevalence of a liberal approach with a limited and not fully clearly defi ned role of the state in the development of the system of crisis adaptation of banks, lack of measures to implement restructuring in the banking sector, the availability of somewhat outdated recommendations is substantiated. The article describes the author’s approach to the formation and implementation of the strategy of restructuring banks in Ukraine from the standpoint of the characteristics of its key elements: the rationale for the need to develop a strategy; defi ning goals and objectives of the strategy; development and selection of strategy options; evaluation of efficiency and selection of priority directions of strategy mplementation; definition of resource availability of the decisions taken; improvement of mechanisms and instruments for regulating restructuring processes in the banking sector as a whole and for its components; monitoring of restructuring processes in the banking sector of the country’s economy. The developed approach allows simultaneously to solve two interrelated tasks: the direct development of the strategy; managing the processes of developing and implementing a strategy.